Sharia Governance and Sharia Compliance Traceability: An Analysis of KSPPS Aminul Ummah Syariatama - Chairul Lutfi; Ely Haryanti; Bintan Dzumirroh Ariny; Ahmad Arif; Denden Soemantri (Civil Officium: Journal of Empirical Studies on Social Science, 2026)
This study analyzes the implementation of Sharia governance at KSPPS Aminul Ummah Syariatama, an Islamic savings and financing cooperative in Depok City, Indonesia, from a Sharia-compliance perspective. Traceability serves as the principal criterion: sharia principles should be traceable from the fatwas of the National Sharia Board of the Indonesian Ulema Council (DSN-MUI) and cooperative regulations for product design, procedures, implementation, supervision, and disclosure. This study employs a descriptive qualitative design based on document analysis of five groups of institutional artefacts for 2022-2023: a qardh financing contract, the EduQard financing standard operating procedure (SOP), financial statements, the Sharia Supervisory Board (DPS) opinion, and marketing materials. Each document is deductively mapped against the relevant DSN-MUI fatwas and the provisions of the Regulation of the Minister of Cooperatives and SMEs Number 8 of 2023, and then classified into three categories with explicit criteria: substantive conformity, administrative alignment needs, and areas requiring clarification. The review indicates conformity in the direction of contract design and the availability of supervisory structures, while the traceability of compliance remains undemonstrated at six points: the definition and structure of the qardh contract, fatwa references and methods in the DPS opinion, disclosure of zakat-infaq-sadaqah funds, SOP presentation, governance of a third-party digital application, and consistency of promotional materials. Sharia compliance in an Islamic cooperative is evidenced by a chain of mutually referring documents. Sharia terminology and the presence of a DPS are entry conditions that require support from internal control, supervisory documentation, and follow-up of recommendations. The analysis is confined to processes and documents and does not assess individual transactions or the personal performance.